Study of the Ethnobotanical Use of Herbal Plants in Blitar District - Huda, Moch Faizul; Meishanti, Ospa Pea Yuanita; Agustin, Dea Arin (Program Study of Biology, Science and Technology Faculty, UIN Maulana Malik Ibrahim Malang, 2023)
Ethnobotanical research was carried out to collect data regarding the use of medicinal plants by the people of Panggungrejo, Blitar Regency. There are 9 types of medicinal plants reported to be used locally for the treatment and control of diseases in humans and livestock. These plants include sangket leaves, betel leaves, castor leaves, dadap spare leaves, lamtoro leaves, kencur, kapok leaves, china ketepeng leaves, and amethyst leaves. Survey results show that leaves are the most frequently harvested part of the plant. Most treatments are done by mashing freshly picked plant parts. These medicinal plants are generally collected from the surrounding environment, gardens and the wild. Even though many modern medicines are available, the people of Panggungrejo, Blitar Regency, still rely heavily on traditional medicinal plants to treat various diseases. Therefore, conservation of medicinal plants in this area is very necessary